Heart failure alters matrix metalloproteinase gene expression and activity in rat skeletal muscle - Carvalho, Robson Francisco; Dariolli, Rafael; Justulin Junior, Luis Antonio; Sugizaki, Mario Mateus; Okoshi, Marina Politi [UNESP]; Cicogna, Antonio Carlos [UNESP]; Felisbino, Sergio Luis; Dal Pai-Silva, Maeli (Blackwell Publishing, 2006)
Heart failure is associated with a skeletal muscle myopathy with cellular and extracellular alterations. The hypothesis of this investigation is that extracellular changes may be associated with enhanced mRNA expression and activity of matrix metalloproteinases (MMP). We examined MMP mRNA expression and MMP activity in Soleus (SOL), extensor digitorum longus (EDL), and diaphragm (DIA) muscles of young Wistar rat with monocrotaline-induced heart failure. Rats injected with saline served as age-matched controls. MMP2 and MMP9 mRNA contents were determined by RT-PCR and MMP activity by electrophoresis in gelatin-containing polyacrylamide gels in the presence of SDS under non-reducing conditions. Heart failure increased MMP9 mRNA expression and activity in SOL, EDL and DIA and MMP2 mRNA expression in DIA. These results suggest that MMP changes may contribute to the skeletal muscle myopathy during heart failure.
Keywords: extracellular matrix; heart failure; metalloproteinases; skeletal muscle; Wistar rats